Exploiting the dividend month premium: evidence from Germany - Kreidl, Felix; Scholz, Hendrik (Journal of Asset Management, 2021)
Dividend payments are firm events on a recurring and predictable basis. High returns in the period between announcement-date and ex-dividend date are the main driver for the so-called dividend month premium, which are positive abnormal returns in months in which corporations are predicted to issue dividend payments. In our empirical analysis of the German stock market, we find a robust dividend month premium, which is particularly high for stocks with positive dividend surprise. Knowing the dates of dividend announcements and payments enable portfolio managers to exploit the dividend month premium. Also taking into account tracking error and transaction costs, we show that simple portfolio-enhancing strategies lead to highly significant abnormal returns.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Cumulative abnormal returns; Dividend month premium; Dividend surprise; Dividends; Exploitation; Outperformance; Portfolio management

Stock-Market Behavior on Ex-Dates: New Insights from German Stocks with Tax-Free Dividend - Kreidl, Felix (International Journal of Financial Studies, 2020)
We examine stock prices and the number of stocks traded around ex-dividend dates of German stocks with tax-free dividend. Tax-free dividends are temporarily tax-exempt, as they reduce the initial purchasing price of a stock. With our analysis of this particular group of German stocks, we can make clear predictions regarding ex-date prices and analyze the number of stocks traded around ex-dates, doing so without the systematic bias of cum-ex trades over time. For XETRA, our empirical results indicate that ex-date prices decline, on average, by the amount of the dividend. We do not find a significant relationship between a stock's price-drop ratio and dividend yield. Further, the empirical analysis suggests that there is no significant correlation between an abnormal number of a stock being traded and its dividend yield. These results are most consistent with tax-motivated reasoning. However, our volume analysis reveals no consistency regarding the abnormal number of stocks traded for multilateral trading facilities.
CRIS-Team WoS Importer:2020-10-30

Withholding-Tax Non-Compliance: The Case of Cum-Ex Stock-Market Transactions - Büttner, Thiess; Holzmann, Carolin; Kreidl, Felix; Scholz, Hendrik (International Tax and Public Finance, 2020)
This paper explores withholding tax non-compliance in the context of dividend taxation. It focuses on a specific type of stock-market transactions around ex-dividend dates, so-called "cum-ex"' trades, which caused considerable revenue losses due to illegitimate tax refunds in Germany and other countries. We use a stylized model of the stock-market equilibrium to analyze the incentives of traders on the German stock market and find that cum-ex trades are only profitable for both buyer and seller in the presence of collusive tax fraud. Our empirical analysis of market data for publicly traded German stocks from 2009 to 2015 confirms that transaction numbers of stocks suitable for cum-ex trades show the expected increase shortly before ex-dividend dates in the period before the tax refunding was reformed. In line with the collusion hypothesis, effects on stock-market prices are not found.<br
Keywords: Tax compliance; Tax evasion; Withholding taxes; Collusion; Tax fraud; Tax refunding; Cum-ex trades; Ex-dividend date; Dividend taxes; Capital gains taxes